BACTERIA AND THEIR IMPACT ON HUMAN HEALTH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Bacteria can have both positive and negative effects on human health. This article analyzes bacteria and their effects on the human body, the microbiome, and diseases caused by pathogenic bacteria. The role of bacteria in the natural microbiome, their interaction with the immune system, and their role in causing infectious diseases are considered. The impact of bacteria on health is discussed using statistical data and scientific research.